The influence of alkylating agents on sulfur-sulfur bonds in per- and polysulfides - Schilling, Danny; Ditrói, Tamás; Barayeu, Uladzimir; Jurányi, Eszter Petra; Nagy, Peter; Dick, Tobias P. (Current opinion in chemical biology, 2023)
Per- and polysulfides are sulfane sulfur species produced inside living cells, in organisms as diverse as bacteria, plants and humans, but their biological roles remain to be fully understood. Unfortunately, due to their reactivity, per- and polysulfides are easily altered, interconverted or lost during the processing and analysis of biological material. Thus, all current analytical methods make use of alkylating agents, to quench reactivity of hydropersulfides and hydropolysulfides and also to prevent free thiols from attacking sulfur chains in hydropolysulfides and dialkyl polysulfides. However, recent findings reveal that alkylating agents can also destroy per- and polysulfides, to varying degrees, depending on the choice of alkylating agent. Here, we discuss the challenges associated with the alkylation of per- and polysulfides, the single most important step for their preservation and detection in biological samples.
Gesehen am 10.12.2024
Available online 18 July 2023